2014
DOI: 10.1038/ismej.2014.188
|View full text |Cite
|
Sign up to set email alerts
|

Natural volcanic CO2 seeps reveal future trajectories for host–microbial associations in corals and sponges

Abstract: Atmospheric carbon dioxide (CO2) levels are rapidly rising causing an increase in the partial pressure of CO2 (pCO2) in the ocean and a reduction in pH known as ocean acidification (OA). Natural volcanic seeps in Papua New Guinea expel 99% pure CO2 and thereby offer a unique opportunity to explore the effects of OA in situ. The corals Acropora millepora and Porites cylindrica were less abundant and hosted significantly different microbial communities at the CO2 seep than at nearby control sites <500 m away. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
241
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(262 citation statements)
references
References 68 publications
15
241
6
Order By: Relevance
“…has been shown to decline significantly. For example, when exposed to high-partial (pCO 2 ) pCO 2 / low-pH conditions found in naturally occurring CO 2 seeps in Papua New Guinea, the coral Acropora millepora demonstrated a 50% reduction in Endozoicomonas-related bacteria in comparison to ambient control sites (55). Furthermore, microbial communities associated with apical lesions on colonies of Belizean P. astreoides were found to be more diverse and harbored a significantly lower relative abundance of OTUs related to Endozoicomonas spp.…”
Section: Discussionmentioning
confidence: 97%
“…has been shown to decline significantly. For example, when exposed to high-partial (pCO 2 ) pCO 2 / low-pH conditions found in naturally occurring CO 2 seeps in Papua New Guinea, the coral Acropora millepora demonstrated a 50% reduction in Endozoicomonas-related bacteria in comparison to ambient control sites (55). Furthermore, microbial communities associated with apical lesions on colonies of Belizean P. astreoides were found to be more diverse and harbored a significantly lower relative abundance of OTUs related to Endozoicomonas spp.…”
Section: Discussionmentioning
confidence: 97%
“…Not only might the observed decrease in these potentially symbiotic taxa during stress events threaten coral resistance to stress, it also may influence coral resilience after the stress is alleviated if Endozoicomonas does not return to its original abundance and function. In a study of volcanic CO 2 seeps where the seawater has naturally reduced pH, researchers found that Acropora millepora and Porites cylindrica contained significantly different microbial communities compared to the same coral species at a control site (>500 m away); for A. millepora this was mainly due to a 50% decrease of this proposed mutualist Endozoicomonas (Morrow et al, 2015). These coral species were also less abundant at the volcanic seeps, potentially due to this loss of symbiont in their microbiomes.…”
Section: Stressors Decrease the Abundance Of The Proposed Bacterial Smentioning
confidence: 99%
“…The gammaproteobacterium Endozoicomonas is emerging as a central member of the coral's microbiome, with flexibility in its lifestyle ( Figure 3D) (Neave et al, 2016(Neave et al, , 2017. Ocean disturbances including elevated temperature and ocean acidification have been shown to disrupt the coral's associated bacteria (Thurber et al, 2009;Meron et al, 2011), including relationships with Endozoicomonas (Morrow et al, 2015). However, some members of this microbiome appear to be stable across large environmental gradients (Hernandez-Agreda et al, 2016).…”
Section: Overview Of Diverse and Emerging Animal-microbiome Study Sysmentioning
confidence: 99%